Performance evaluation of low-thrust rocket nozzles of various geometries / Ahmad Hussein Abdul Hamid ... [et al.] - Abdul Hamid, Ahmad Hussein; Salleh, Zuraidah; Ahmad Termizi, Ahmad Tamimi; Muhammad, Mohamad Amirul; Mohammed Sapardi, Mohd Azan (Universiti Teknologi MARA, 2022)
Issues of viscous loss in rocket nozzle become increasingly more important as the thrust chamber is reduced in size. A properly designed nozzle is critical since small geometrical differences can result in dramatically modified performance. The present study analyzes the performance of conical converging-diverging nozzle for low-thrust rocket application. A total of five nozzles with different area ratio and divergence length were numerically tested; two optimum area ratio nozzles, one underexpanding nozzle and two overexpanding nozzles. The main aim is to analyze the flow phenomena of compressible gas flows within these nozzles and its relation to the rocket performance (i.e. thrust). The axisymmetric flow problems are numerically solved using a well-validated software with the Spalart-Allmaras turbulence model is employed to model the effect of turbulent on the flow. The results revealed technique of eliminating flow separation and obviously, knowledge of the point of separation is essential for performance enhancement. The elimination of flow separation inside the overexpanding nozzle by means of truncating it at a point of separation increases the thrust produced by 18% for a relatively low combustion pressure. It is anticipated that the thrust enhancement would be greater for a higher nozzle pressure ratio (NPR, i.e. the ratio of combustion chamber total pressure and atmospheric static Issues of viscous loss in rocket nozzle become increasingly more important as the thrust chamber is reduced in size. A properly designed nozzle is critical since small geometrical differences can result in dramatically modified performance. The present study analyzes the performance of conical converging-diverging nozzle for low-thrust rocket application. A total of five nozzles with different area ratio and divergence length were numerically tested; two optimum area ratio nozzles, one underexpanding nozzle and two overexpanding nozzles. The main aim is to analyze the flow phenomena of compressible gas flows within these nozzles and its relation to the rocket performance (i.e. thrust). The axisymmetric flow problems are numerically solved using a well-validated software with the Spalart-Allmaras turbulence model is employed to model the effect of turbulent on the flow. The results revealed technique of eliminating flow separation and obviously, knowledge of the point of separation is essential for performance enhancement. The elimination of flow separation inside the overexpanding nozzle by means of truncating it at a point of separation increases the thrust produced by 18% for a relatively low combustion pressure. It is anticipated that the thrust enhancement would be greater for a higher nozzle pressure ratio (NPR, i.e. the ratio of combustion chamber total pressure and atmospheric static pressure). With the demonstrated performance enhancement, this work serves as a driver for further nozzle enhancement using this technique.